The systematics of the pseudoscorpion genus Indohya (Pseudoscorpiones: Hyidae) in Australia - Harvey, Mark S.; Burger, Mieke A. A.; Abrams, Kym M.; Finston, Terrie L.; Huey, Joel A.; Perina, Giulia (Zootaxa, 2023)
The pseudoscorpion genus Indohya Beier, 1974 is known to occur in three Gondwanan fragments around the Indian Ocean—southern India, Madagascar and north-western Australia—suggesting that the genus had evolved prior to the breakup of Gondwana and was present on each landmass as they rifted apart during the Mesozoic. The Australian fauna is the most diverse, with nine species previously described from Cape Range and the Kimberley region of north-western Australia. The present study documents the genus Indohya in Australia using a combination of morphology and DNA sequence data. We found a total of 36 species, including 27 new species. The majority of the Pilbara fauna consist of blind troglobites collected from subterranean ecosystems, with an additional three eyed species from epigean habitats. The new species consist of one from Cape Range (I. anastomosa Harvey & Burger, n. sp.), 21 from the Pilbara (I. adlardi Harvey & Burger, n. sp., I. alexanderi Harvey & Burger, n. sp., I. aphana Harvey & Burger, n. sp., I. aquila Harvey & Burger, n. sp., I. arcana Harvey & Burger, n. sp., I. arnoldstrongi Harvey & Burger, n. sp., I. boltoni Harvey & Burger, n. sp., I. cardo Harvey & Burger, n. sp., I. catherineae Harvey & Burger, n. sp., I. cockingi Harvey & Burger, n. sp., I. cribbi Harvey & Burger, n. sp., I. draconis Harvey & Burger, n. sp., I. furtiva Harvey & Burger, n. sp., I. incomperta Harvey & Burger, n. sp., I. jessicae Harvey & Burger, n. sp., I. lynbeazlyeae Harvey & Burger, n. sp., I. morganstrongi Harvey & Burger, n. sp., I. rixi Harvey & Burger, n. sp., I. sagmata Harvey & Burger, n. sp., I. scanloni Harvey & Burger, n. sp. and I. silenda Harvey & Burger, n. sp.) and five from the Kimberley (I. currani Harvey & Burger, n. sp., I. finitima Harvey & Burger, n. sp., I. julianneae Harvey & Burger, n. sp., I. karenae Harvey & Burger, n. sp. and I. sachsei Harvey & Burger, n. sp.). The study is augmented with sequence data from 29 species of Indohya, including all of the 24 species recorded from the Pilbara and Cape Range, and five of the 12 known Kimberley species. Seven clades recovered during the molecular analysis are only represented by nymphs, but we used COI sequence data to diagnose these species in the absence of adult morphological data.